2015
DOI: 10.1530/erc-15-0318
|View full text |Cite
|
Sign up to set email alerts
|

Developing treatment for adrenocortical carcinoma

Abstract: Cancer of the adrenal cortex (ACC) is a rare endocrine malignancy with limited treatment options. Patients typically present with autonomous hormonal overproduction and/or a large abdominal mass. Hormonal assays and medical imaging can be diagnostic, but urinary steroid profiling might be a more sensitive technique to assess malignancy in adrenal tumours. The stage of the disease at diagnosis is the most important prognostic factor. The current staging system needs refinement, especially to separate aggressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 97 publications
1
24
0
Order By: Relevance
“…Hypercortisolism (Cushing syndrome) or mixed Cushing and virilizing syndromes are observed in the majority of these patients. Pure androgen excess is less frequent while estrogen or mineralocorticoid excess are very rare (13,18,19,20,21,22). Non-specific symptoms from an abdominal mass include abdominal discomfort (nausea, vomiting, abdominal fullness) or back pain.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Hypercortisolism (Cushing syndrome) or mixed Cushing and virilizing syndromes are observed in the majority of these patients. Pure androgen excess is less frequent while estrogen or mineralocorticoid excess are very rare (13,18,19,20,21,22). Non-specific symptoms from an abdominal mass include abdominal discomfort (nausea, vomiting, abdominal fullness) or back pain.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Adrenocortical carcinoma is an aggressive disease, and the stage of the tumor at diagnosis is the factor with the greatest impact on prognosis (Kerkhofs et al 2015). Fay and coworkers investigated the expression of PD-L1 in adrenocortical carcinoma tissues (Fay et al 2015).…”
Section: Adrenocortical Carcinomamentioning
confidence: 99%
“…11,12 If genomic profiling is expected to become clinically relevant in the future, the KI67 proliferation index seems the best prognostic tool currently available. 13 Regarding the targeted therapies, no study has demonstrated any benefit with agents blocking molecular pathways such as EGFR, VEGF, mTOR, IGF-1R or FGFR in advanced disease. [14][15][16][17][18] The concept that cancer cells can exploit the immune checkpoint pathway to evade the immune system and allow tumor growth has been known for decades.…”
Section: Introductionmentioning
confidence: 99%